2009
DOI: 10.1593/tlo.09124
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA Expression Patterns in Hepatoblastoma Patients

Abstract: Liver cancers in children are rare representing only 1.1% of malignancies, with an annual incidence rate of 1.5 cases per million. Hepatoblastoma and hepatocellular carcinomas are the most common malignancies of the liver occurring in young people aged 15 years or younger. Molecular basis of both tumors are still unclear, and common markers (i.e., CTNNB1, APC, IGF-2) are not always useful in the characterization of sporadic forms; in this respect, microRNA recently associated with carcinogenesis could play a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Contrarily, miR‐624‐5p, let‐7i‐3p, miR‐885‐5p, and miR‐449b‐3p were significantly down‐regulated in tumors (Fig. 3A), supporting previous results for miR‐885‐5p 14. Relating miRNA expression to the clinical information, we noticed that low expression of miR‐885‐5p was correlated with the presence of multiple nodules and an advanced stage of the disease (Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Contrarily, miR‐624‐5p, let‐7i‐3p, miR‐885‐5p, and miR‐449b‐3p were significantly down‐regulated in tumors (Fig. 3A), supporting previous results for miR‐885‐5p 14. Relating miRNA expression to the clinical information, we noticed that low expression of miR‐885‐5p was correlated with the presence of multiple nodules and an advanced stage of the disease (Fig.…”
Section: Resultssupporting
confidence: 86%
“…This decrease was previously reported for miR‐885‐5p,14 and we further found that an miR‐885‐5p decrease is associated with advanced HBL (Fig. 3B) and inversely correlates with beta‐catenin mRNA in CTNNB1 ‐deleted HBL tumors.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations